KEPERCAYAAN MASYARAKAT TERHADAP INFORMASI TRADISIONAL DAN MODERN PADA PERISTIWA BENCANA ALAM - Damayanti Wardyaningrum (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2018)
The purpose of the research is to identify the local people believe in current information or traditional information of the natural disaster of Merapi mountain in Central Java as one of the mostactive volcanoes in the world. Concept use is information and natural disaster. The research uses post-positivist paradigm with the survey, interview, and observation for data gathering regarding the big eruption in 2010. The results show more than half of local people believe in traditional information than modern information regarding the natural disaster. The differences of local people believe are base on the level of education, age and the role in public. Local citizen believes to traditional information mostly are old people their education background from the elementary level, and has no role in public.On the other hand for the local citizen that believe to modern information are young people, from middle-level education and some of them has a role in public.The perception of traditional information occurs since the old people have some experiences of last volcanic eruption, and more listen to the people they closed and less of literation regarding disaster mitigation. The differences of belief to both traditional and modern information are not statistically significant is an opportunity for integrating traditional and modern information for disaster risk reduction. This research contributes to give insight of the difference of traditional  and modern information on disaster events.